The Effects of Hyperlipidemia on Postoperative Cognitive Dysfunction in Patients Undergoing Laparoscopic Gynecological Tumor Surgery - Shen H; Xiong Y; Liang Y; Liu Z; Guo L; Qin Y; He J; Lin F (Neuropsychiatric Disease and Treatment)
Honglei Shen,1,2,* Yao Xiong,2,* Yubing Liang,1 Zhen Liu,1 Liang Guo,1 Yi Qin,2 Jing He,1,2 Fei Lin1 1Department of Anesthesiology, Guangxi Medical University Cancer Hospital, Guangxi Zhuang Autonomous Region, Nanning, People’s Republic of China; 2Guangxi Medical University, Guangxi Zhuang Autonomous Region, Nanning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fei Lin, Guangxi Medical University Cancer Hospital, 71 hedi Road, Qingxiu District, Nanning, Guangxi, CA 530021, People’s Republic of China, Tel +8613707886172, Email linfei@gxmu.edu.cnBackground: POCD is a common postoperative complication associated with anesthesia and surgery. Its occurrence reduces the quality of life after surgery and increases the risk of death and disability. Related studies demonstrated that hyperlipidemia could affect the occurrence and development of patients’ cognitive dysfunction. However, the association between hyperlipidemia and POCD has not been well examined.Methods: A total of 98 patients were divided into hyperlipidemia group and normal lipid group based on blood lipid level. Minimum Mental State Examination was used to evaluate the preoperative cognitive status. The patients were assessed with the Montreal Cognitive Assessment 1 day before operation and 7 days after operation. The Telephone Interview for Cognitive Status-Modified was applied to evaluate the cognitive ability 1 and 3 months after surgery. We analyzed the incidence of POCD and its potential risk factors according to the scores on each scale after operation.Results: A total of 98 patients including 52 patients in the hyperlipidemia group and 46 patients in the normal blood lipid group completed all postoperative follow-up. POCD occurred in 27 patients 7 days after surgery, including 19 patients (36.54%) in the hyperlipidemia group and 8 patients (17.39%) in the normal group. One month after surgery, 23 patients experienced POCD, with 17 (32.69%) in the hyperlipidemia group and 6 (13.04%) in the normal group. And three months after surgery, 20 patients experienced POCD, including 14 (26.92%) in the hyperlipidemia group and 6 (13.04%) in the normal group. Through univariate and multivariate regression analysis, we found that age and total cholesterol level were significantly associated with the occurrence of POCD.Conclusion: Preoperative hyperlipidemia was associated with the occurrence of POCD 7 days and 1 month after laparoscopic gynecologic tumor surgery. Age and preoperative hypercholesterolemia were considered independent risk factors for POCD development.Keywords: POCD, lipid metabolism disorders, perioperative management, laparoscopic surgery